2020
DOI: 10.1371/journal.pone.0233212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of direct-acting antiviral therapy for hepatitis C–related hepatocellular carcinoma

Abstract: With the introduction of direct-acting antiviral (DAA) agents, hepatitis C virus (HCV) treatment has dramatically improved. However, there are insufficient data on the benefits of DAA therapy in hepatocellular carcinoma (HCC). The purpose of this study was to investigate the outcome of patients who received DAA therapy after HCC treatment. We retrospectively reviewed patients with HCV-related HCC in a single medical center, and the outcome of patients with or without DAA therapy was analyzed. In total, 107 HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
(42 reference statements)
1
14
2
Order By: Relevance
“…The rates of SVR were very satisfactory, 255 demonstrating that the treatment reached a high cure rate with an average of 95.5% with DAA 256 incorporated into SUS (87% to 100%), being the largest study carried out to date in Latin America. Similar data were found in other studies [9,19,20] .…”
Section: Resultssupporting
confidence: 93%
“…The rates of SVR were very satisfactory, 255 demonstrating that the treatment reached a high cure rate with an average of 95.5% with DAA 256 incorporated into SUS (87% to 100%), being the largest study carried out to date in Latin America. Similar data were found in other studies [9,19,20] .…”
Section: Resultssupporting
confidence: 93%
“…Similar results were found by Conti et al [ 14 ] in a single-center retrospective cohort study, with a recurrence rate of HCC after DAAs of 28.81%. Contrasting results were reported by Lin et al [ 59 ] in a recently published retrospective study which included 107 patients with HCV-related HCC, of whom 60 received DAA therapy after treatment for HCC. After a median follow-up of 20 mo, 37.1% patients had HCC recurrence after DAAs.…”
Section: Hcc Recurrence After Daa Therapycontrasting
confidence: 67%
“…Patients with BCLC-B/C HCC should have preserved liver function (Child-Pugh A or B 7 points without clinical ascites and/or encephalopathy) and all cirrhosis complications, such as variceal bleeding, under control. The limited published information [10,30,[34][35][36][37] regarding DAA treatment in this population is described in Supplementary Table 2. Chi et al, Ogawa et al, and Dang et al [35,37] were the only cohorts that reported SVR in BCLC-B/C/D patients ranging from 77.8-100%.…”
Section: Rate Of Svr In Hcc Patientsmentioning
confidence: 99%